Penerapan Model Cooperative Learning dengan Media Kartu Bergambar terhadap Hasil Belajar Materi Jaringan Hewan Siswa Kelas XI MIA 2 MAN 10 Jombang - hasna lailil ma'rifah (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2020)
Abstract This study aims to determine the learning outcomes of class XI MIA 2 student in MAN 10 Jombang with cooperative learning models. This type of research is quantitative research using one shot case study research design. Class XI MIA 2 research at MAN 10 Jombang. This study shows the average learning outcomes of animal tissue material that is 76,419, after remidial held an average increase to 90,2. While student’s learning completeness is 67% which 67% are in the range of values 66-79% with good criteria. It can be concluded that the cooperative learning model by involving picture card media can help student’s achieve mastery learning. Keywords : cooperative learning, learning outcomes, animal tissue, picture card.